Facts about Magnesium Sulfate: Time to Revise the Safety Concern in Obstetric Use (Journal of Enam Medical College, 2014)
Magnesium sulfate (MgSO4) is the agent most commonly used for treatment of eclampsia and prevention of eclampsia in patients with severe pre-eclampsia. Another commonly practiced offlabel use of this drug is in preventing preterm labor in pregnant women where the duration of the treatment might be more than one week. It is usually given either by intramuscular or intravenous route. After administration, about 40% of plasma magnesium is bound with protein. The unbound magnesium ion diffuses into the extravascular extracellular space and then diffuses into bone. It also crosses the placenta and fetal membranes and then diffuses into the fetus and amniotic fluid. Magnesium is almost exclusively excreted in the urine; 90% of the dose is excreted during the first 24 hours after an intravenous infusion of MgSO4. The clinical effect and toxicity of MgSO4 can be linked to its concentration in plasma. A concentration of 1.83.0 mmol/L has been suggested for treatment of eclampsia. The actual magnesium dose and concentration needed for prophylaxis have never been estimated. Maternal toxicity is rare when MgSO4 is carefully administered and monitored. Deep tendon reflexes, respiratory rate, urine output and serum concentrations are the most common variables for monitoring the toxic effect. Currently the United States (US) Food and Drug Administration (FDA) is advising health care professionals against using MgSO4 injection for more than 57 days to stop preterm labor in pregnant women (off-label use). Administration of MgSO4 injection to pregnant women for more than 57 days may lead to low calcium levels and bone problems in the fetus, including osteopenia and fractures. The harmful effect in the fetus with the shortest duration is not established. In light of this new safety information, the drug label for MgSO4 injection, USP 50% has also been changed, including changing the pregnancy category to D from A and denoting the effect as New teratogenic effects. Similarly, the manufacturers of other MgSO4 injection products have made similar changes to their drug labels. In this review, the currently available knowledge of the pharmacokinetics of MgSO4 and its clinical usage for women with pre-eclampsia and eclampsia, its off-label use and safety concern regarding the warning announced by the FDA will be outlined. DOI: http://dx.doi.org/10.3329/jemc.v4i3.20957 J Enam Med Col 2014; 4(3): 177-183